Effect of compensation doping on the electrical and optical properties of mid-infrared type-II InAs/GaSb superlattice photodetectors - 王永宾 徐云 张宇 迂修 宋国峰 陈良惠 (Chinese physics B, 2011)
This paper presents a theoretical study on the electrical and optical properties of mid-infrared type-II InAs/GaSb superlattices with different beryllium concentrations in the InAs layer of the active region. Dark current, resistancearea product, absorption coefficient and quantum efficiency characteristics are thoroughly examined. The superlattice is residually n-type and it becomes slightly p-type by varying beryllium-doping concentrations, which improves its electrical performances. The optical performances remain almost unaffected with relatively low p-doping levels and begin to deteriorate with increasing p-doping density. To make a compromise between the electrical and optical performances, the photodetector with a doping concentration of 3 ×10^15 cm-3 in the active region is believed to have the best overall performances.